The Influence Of Market Share, Density, Investment Yield, And Gross Contribution To The Total Assets Of Islamic Insurance Companies In Indonesia In 2018-2022 - Rahmad Sahputra Tanjung; Nur Ahmadi Bi Rahmani; Fauzi Arif Lubis (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to determine the effect of market share, density, investment yield, and gross contribution to the total assets of Islamic insurance companies in Indonesia in 2018-2022. The research method uses quantitative associative multiple linear regression using secondary data from the Financial Services Authority publication. The type of data uses time series. The sample of Islamic insurance companies listed in IKNB Syariah for the period 2018-2022 with a total of 58 companies. Data processed using SPSS. The results of market share research have a significant positive effect on the total assets of Islamic Insurance Companies in Indonesia in 2018-2022. Density has no significant effect, and investment yield has a significant positive effect, gross contribution has no significant effect. Meanwhile, based on the results of analysis using SPSS version 23, all independent variables, namely Market Share, Density, Investment Yield, and Gross Contribution together have a significant effect on the dependent variable. Simultaneously, when market share, density, investment yield, and gross contribution function together, they create a favourable environment for the growth of total assets. The combined effect of these factors provides an overview of how economic and strategic factors can influence asset accumulation in the context of the analysed market or industry.